2012
DOI: 10.1007/s00330-012-2412-7
|View full text |Cite
|
Sign up to set email alerts
|

Observer training for computer-aided detection of pulmonary nodules in chest radiography

Abstract: ObjectivesTo assess whether short-term feedback helps readers to increase their performance using computer-aided detection (CAD) for nodule detection in chest radiography.MethodsThe 140 CXRs (56 with a solitary CT-proven nodules and 84 negative controls) were divided into four subsets of 35; each were read in a different order by six readers. Lesion presence, location and diagnostic confidence were scored without and with CAD (IQQA-Chest, EDDA Technology) as second reader. Readers received individual feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In previous studies, CAD stand-alone sensitivity was 59% with FPR 1.9 FP/image. [ 5 ] The study of Schalekamp et al, not only showed a higher sensitivity of 74% but also in turn a higher FPR of 1/image. [ 2 ] In another study comparing different versions of CAD systems, the sensitivity of the newest tested version OnGuard 5 was 64.4% and the FPR was 2/image.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, CAD stand-alone sensitivity was 59% with FPR 1.9 FP/image. [ 5 ] The study of Schalekamp et al, not only showed a higher sensitivity of 74% but also in turn a higher FPR of 1/image. [ 2 ] In another study comparing different versions of CAD systems, the sensitivity of the newest tested version OnGuard 5 was 64.4% and the FPR was 2/image.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decades, digital chest radiography has iteratively and incrementally improved, with numerous processing tools being developed to support radiologists in the detection of pathological findings [ 2 , 4 , 5 ]. Most of these tools have been implemented to improve nodule detection, including digital tomosynthesis [ 6 8 ], dual energy and temporal subtraction techniques [ 9 11 ], computer-aided detection systems [ 12 , 13 ] and dark-field CXR. More recently, dark-field CXR has been demonstrated to be a valuable complementary tool for the assessment of pulmonary infiltrates, cardiomegaly and hemopericardium [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%